2019
DOI: 10.1051/epjconf/201919702010
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric monitoring using the Cherenkov Transparency Coefficient for the Cherenkov Telescope Array

Abstract: The future ground-based gamma-ray observatory, the Cherenkov Telescope Array (CTA) will require reliable monitoring of the atmosphere which is an inherent part of the detector. We discuss here the implementation of the extended method of the Cherenkov Transparency Coeffcient for the atmospheric calibration for the CTA. The method estimates the atmospheric transmission of Cherenkov light, relying on the measurement of the rates of cosmic ray-induced air showers that trigger different pairs of telescopes. We exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The transparency is normalized so that T = 1 corresponds to no aerosol attenuation. A single model of the molecular density of the atmosphere is assumed as it has been shown that the CTC is not sensitive to the seasonal variations of the local density profile [10].…”
Section: Atmospheric Monitoringmentioning
confidence: 99%
“…The transparency is normalized so that T = 1 corresponds to no aerosol attenuation. A single model of the molecular density of the atmosphere is assumed as it has been shown that the CTC is not sensitive to the seasonal variations of the local density profile [10].…”
Section: Atmospheric Monitoringmentioning
confidence: 99%